2017
DOI: 10.1200/jco.2016.71.5904
|View full text |Cite|
|
Sign up to set email alerts
|

Brigatinib in Patients With Crizotinib-Refractory Anaplastic Lymphoma Kinase–Positive Non–Small-Cell Lung Cancer: A Randomized, Multicenter Phase II Trial

Abstract: Most crizotinib-treated patients with anaplastic lymphoma kinase gene (ALK)-rearranged non-smallcell lung cancer (ALK-positive NSCLC) eventually experience disease progression. We evaluated two regimens of brigatinib, an investigational next-generation ALK inhibitor, in crizotinib-refractory ALK-positive NSCLC. Patients and MethodsPatients were stratified by brain metastases and best response to crizotinib. They were randomly assigned (1:1) to oral brigatinib 90 mg once daily (arm A) or 180 mg once daily with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
479
1
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(499 citation statements)
references
References 28 publications
9
479
1
10
Order By: Relevance
“…The phase II ALTA trial therefore looked at two different dosing schedules at either 90 mg daily (group A) or 90 mg daily with escalation to 180 mg daily after 7 days (group B). The ORR was 45% in group A and 54% in group B [27]. The median duration of response was 13.8 months in group A and 11.1 months in group B.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…The phase II ALTA trial therefore looked at two different dosing schedules at either 90 mg daily (group A) or 90 mg daily with escalation to 180 mg daily after 7 days (group B). The ORR was 45% in group A and 54% in group B [27]. The median duration of response was 13.8 months in group A and 11.1 months in group B.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Clinical data from the brigatinib phase II ALTA clinical trial (NCT02094573) showed ORRs of 45% and 54% for doses of 90 and 180 mg daily, respectively (14). The most noticeable adverse event associated with brigatinib is early pulmonary toxicity.…”
Section: Acquired Resistance To Crizotinib and Development Of Next Gementioning
confidence: 99%
“…Subsequent study schema have therefore incorporated a dose escalation phase with a starting dose of 90 mg orally daily for 7 days, then increasing to 180 mg daily. Outside of pulmonary concerns, the drug is otherwise well tolerated and with serious gastrointestinal side effects and headaches occurring in a minority of cases (14). Brigatinib received regulatory approval for use in crizotinibresistant or intolerant patients in 2017.…”
Section: Acquired Resistance To Crizotinib and Development Of Next Gementioning
confidence: 99%
See 1 more Smart Citation
“…Additional ALK inhibitor approved in April 2017 was Brigatinib [12] (Table 1), which demonstrated PFS of 8.8 months with the daily dose 90 mg, and 11.1 months with the 180 mg dose, although the starting dose will be 90 mg. The overall RR was 46% and 54% in each arm, respectively.…”
Section: Future Alk Inhibitorsmentioning
confidence: 99%